1998
DOI: 10.1007/s001270050208
|View full text |Cite
|
Sign up to set email alerts
|

Understanding causal paths between mental illness and violence

Abstract: The stigma associated with mental illness is a major concern for patients, families, and providers of health services. One reason for the stigmatization of the mentally ill is the public perception that they are violent and dangerous. Although, traditionally, mental health advocates have argued against this public belief, a recent body of research evidence suggests that patients who suffer from serious mental conditions are more prone to violent behaviour than persons who are not mentally ill. It is a point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 61 publications
1
37
1
3
Order By: Relevance
“…Previous research strongly suggests a relationship between severe mental illness and criminality (Arboleda-Floréz & Crisanti, 1998;Hodgins, Mednick, Brennan, Schulsinger & Engberg, 1996;Hodgins, Alderton, Cree, Aboud, & Mak, 2007). Findings from the Epidemiological Catchment Area study (ECA) concluded that comorbidity of addictive problems and severe mental disorder was approximately 90% in Downloaded by [University of Kent] at 08:56 04 December 2014 the prison population (Swanson et al, 2000).…”
Section: Mental Illness and Criminalitymentioning
confidence: 98%
“…Previous research strongly suggests a relationship between severe mental illness and criminality (Arboleda-Floréz & Crisanti, 1998;Hodgins, Mednick, Brennan, Schulsinger & Engberg, 1996;Hodgins, Alderton, Cree, Aboud, & Mak, 2007). Findings from the Epidemiological Catchment Area study (ECA) concluded that comorbidity of addictive problems and severe mental disorder was approximately 90% in Downloaded by [University of Kent] at 08:56 04 December 2014 the prison population (Swanson et al, 2000).…”
Section: Mental Illness and Criminalitymentioning
confidence: 98%
“…It is difficult to prove a causal link between risk factors and violence [43], but the overall findings highlight that in acute mental health populations there is a need to focus on what the person has done, (past and recent history of violence) what the person is (angry, impulsive, aggressive) and what the person has (personality disorder, psychopathy) [20] and substance misuse should remain a focus in risk assessment in both males and females. Although efforts have been made to develop an evidence-based actuarial tool for clinicians based on the findings of MacVRAS [28] further validation studies are still required and the challenge remains for clinicians in acute mental health services to apply the findings from this study and others into practice.…”
Section: Measurementioning
confidence: 99%
“…Among such possible problems are of course violent or threatening acts ± or the perception by others of a threat when it is more or less contained in the interpersonal situation and dynamics, as observed by ± and fears for the safety of the person who will become a candidate for the diagnostic process. This issue has not been raised in the dangerousness assessment literature, except recently by Arboleda-Florez et al (1998). These authors characterised the problem as`confounding by definition', which seriously mars any causal inferences that could be made based on empirical evidence showing a statistical association between mental illness and violence'.…”
Section: The Question Of the Relationship Between Mental Illness And mentioning
confidence: 99%